The influence of Qing glass technology on Qianlong and Jiaqing painted enamel copperwares - Norris, Dana; Delbey, Thomas (Elsevier, 2023)
The white enamel surfaces of ten Chinese painted enamels dating to the Qianlong and Jiaqing periods (1736–1820) were studied with Laser Ablation Inductively Coupled Mass Spectrometry (LA-ICPMS). These enamels are opacified with lead arsenate, a dramatic change in technology from fluorite and lead stannite opacification used in Chinese and European enamels before the 18th century. The primary goal of this project was to test the hypothesis that boron is a significant component in Chinese painted enamels. Borax (Na₂[B₄O₅(OH)₄]·8H₂O) was used by glassmakers working in the imperial workshops in Beijing in the mid-18th century, and boron has been detected in some examples of Qing glass and enamels. Quantitative analyses of major, minor, and trace level elements were carried out with LA-ICPMS. Three compositional groups were identified by the amount of borax in the enamel: high borax (at 6.7% B2O3), low borax (up to 1.3% B2O3), and borax free. The results show that it is possible to distinguish between objects made in Beijing and Guangzhou through elemental analysis, and that there are two distinct compositional groups of Chinese painted enamel produced in Guangzhou during this period.
Keywords: LA-ICPMS; Chinese painted enamel; Glass; Copper; Porcelain; Cloisonné